British crime survey, 2004-2005 (Crime Survey for England and Wales, 2022)
The Crime Survey for England and Wales (CSEW) asks a sole adult, in a random sample of households, about their, or their household's, experience of crime victimisation in the previous 12 months. These are recorded in the victim form data file (VF). A wide range of questions are then asked covering demographics and crime-related subjects such as attitudes to the police and the criminal justice system (CJS) these variables are contained within the non-victim form (NVF) data file.